THE RELATIONSHIP BETWEEN KNOWLEDGE AND COMMUNITY ACTIONS REGARDING MALARIA INCIDENCE AMONG RESIDENTS LIVING IN KOYA TIMUR SUBDISTRICT, PAPUA PROVINCE - Lembang, Vany; Muliono, Ari Christy; Prabantoro, Benedictus Triagung Ruddy (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Based on data from the Ministry of Health, malaria cases in Indonesia have decreased; however, there are still three provinces that have not been eliminated, namely Papua, West Papua, and Maluku. The reported cases of malaria in Koya Timur Subdistrict amount to a total of 167 cases. Knowledge and community actions have an influence on malaria incidence, making it crucial to enhance the public’s understanding of the causes of malaria. The objective of this study was to ascertain the relationship between knowledge and community actions regarding malaria incidence among residents of Koya Timur Subdistrict, Papua Province. The research methodology employed was an analytical observational method with a cross-sectional research design the sampling, based on respondents meeting inclusion criteria. The research instruments included a questionnaire and a checklist. The data analysis was conducted using the Spearman test. The research findings showed that of the 61 respondents who completed the questionnaire, 54.1% were male and 45.9% were female. The results indicated that 57.4% had adequate knowledge about malaria, and 65.6% practiced adequate malaria prevention measures. The correlation analysis showed a significant p-value of 0.014 with a correlation coefficient (r) of 0.313. It can be concluded that there is a relationship between community knowledge and actions related to the incidence of malaria among residents in Koya Timur Subdistrict, Papua Province.